Development of a self-healing soft pneumatic actuator: a first concept. (7th July 2015) - Terryn, Seppe; Mathijssen, Glenn; Brancart, Joost; Lefeber, Dirk; Assche, Guy Van; Vanderborght, Bram
Abstract: Inspired by the intrinsic softness and the corresponding embodied intelligence principles, soft pneumatic actuators (SPA) have been developed, which ensure safe interaction in unstructured, unknown environments. Due to their intrinsic softness, these actuators have the ability to resist large mechanical impacts. However, the soft materials used in these structures are in general susceptible to damage caused by sharp objects found in the unstructured environments. This paper proposes to integrate a self-healing (SH-) mechanism in SPAs, such that cuts, tears and perforations in the actuator can be self-healed. Diels–Alder (DA-) polymers, covalent polymer network systems based on the thermoreversible DA-reaction, were selected and their mechanical, as well as SH-properties, are described. To evaluate the feasibility of developing an SPA constructed out of SH-material, a single cell prototype, a SH-soft pneumatic cell (SH-SPC), was constructed entirely out of DA-polymers. Exploiting the SH-property of the DA-polymers, a completely new shaping process is presented in this paper, referred to as 'shaping through folding and self-healing'. 3D polygon structures, like the cubic SH-SPC, can be constructed by folding SH-polymer sheet. The sides of the structures can be sealed and made airtight using a SH-procedure at relatively low temperatures (<90 °C). Both the (thermo) mechanical and SH-properties of the SH-SPC prototype were experimentally validated and showed excellent performances. Macroscopic incisions in the prototype were completely healed using a SH-procedure (<70 °C). Starting from this single-cell prototype, it is straight-forward to develop a multi-cell prototype, the first SPA ever built completely out of SH-polymers.